Does TikTok Shape the Communication Behavior of Emerging Human Capital? A PLS-SEM Analysis of For You Page Exposure among University Students - Nowly Kursinta Manik; Veranus Sidharta (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2026)
This study examines whether exposure to TikTok's For You Page shapes the communication behavior of university students as emerging human capital. The study employed a quantitative explanatory design using a survey method involving 106 students from private universities in Depok City, Indonesia. Data were collected via an online questionnaire using a five-point Likert scale and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) in SmartPLS 4. The model tested the effect of TikTok For You Page exposure on students' communication behavior, including language style, self-expression, interaction patterns, communication responses, and digital communication practices. The results show that TikTok For You Page exposure did not significantly influence students' communication behavior, as indicated by a t-statistic of 0.974 and a p-value of 0.330. The R-square value of 0.146 indicates that TikTok exposure explained only 14.6% of the variance in communication behavior, while the remaining variance was influenced by other factors outside the model. These findings suggest that communication behavior is shaped not only by media exposure intensity but also by digital literacy, social environment, content type, and individual interpretation. The study contributes to current discussions in digital media and human capital research.